Biological and Mechanical Factors and Epigenetic Regulation Involved in Tendon Healing - Zhi Jie Li; Qian Qian Yang; You Lang Zhou (Stem Cells International)
Tendons are an important part of the musculoskeletal system. Connecting muscles to bones, tendons convert force into movement. Tendon injury can be acute or chronic. Noticeably, tendon healing requires a long time span and includes inflammation, proliferation, and remodeling processes. The mismatch between endogenous and exogenous healing may lead to adhesion causing further negative effects. Management of tendon injuries and complications such as subsequent adhesion formation are still challenges for clinicians. Due to numerous factors, tendon healing is a complex process. This review introduces the role of various biological and mechanical factors and epigenetic regulation processes involved in tendon healing.